STRATEGI KOMUNIKASI HUMAS MELALUI MEDIA SOSIAL INSTAGRAM DALAM MEMBANGUN CITRA POSITIF PEMERINTAH KOTA DENPASAR - Ni Luh Putu Diah Desvi Arina; I Wayan Wastawa; I Wayan Suyanta (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
Organizational image is defined as the public's perception of an organization in its public memory. This makes a positive image must be built and maintained by an organization, institution including government agencies. This study aims to analyze the management of government social media, especially public relations through Instagram social media in building a positive image of the Denpasar City Government. This research uses a qualitative approach which is carried out through content observation on the Denpasar City Public Relations account, namely the @joyful.denpasar account and conducting interviews with the Head of Public Relations and Leadership Communications, Denpasar City Government, interviews with Instagram account managers @joyful.denpasar, and public relations consultants. The next process is data analysis and described in the form of an actual explanation. The results showed that the process of implementing the Public Relations communication strategy through Instagram social media in building a positive image of the Denpasar City Government, went through several stages starting from planning the communication strategy, implementing the communication strategy, to the evaluation stage. The obstacles encountered by Denpasar City Public Relations in implementing a communication strategy in building a positive image, namely internal obstacles, including the lack of human resources for communication graduates, and the limited availability of adequate tools, while external obstacles, namely there are still fake accounts or fake accounts. However, there are several steps taken by Denpasar City Public Relations to overcome these obstacles, namely first planning, organizing, actuating, and controlling. So that these obstacles can be minimized. The implications of the Denpasar City Public Relations communication strategy through Instagram social media in building a positive image, including making account activityjoyful. denpasar as an account that provides positive information, and becomes the official information media for the Denpasar city government that is able to provide reliable, up-to-date and up-to-date information.